2023
DOI: 10.3389/frtra.2023.1160752
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus—why pharmacokinetics matter in the clinic

Lino Henkel,
Ulrich Jehn,
Gerold Thölking
et al.

Abstract: The calcineurin inhibitor (CNI) Tacrolimus (Tac) is the most prescribed immunosuppressant drug after solid organ transplantation. After renal transplantation (RTx) approximately 95% of recipients are discharged with a Tac-based immunosuppressive regime. Despite the high immunosuppressive efficacy, its adverse effects, narrow therapeutic window and high intra- and interpatient variability (IPV) in pharmacokinetics require therapeutic drug monitoring (TDM), which makes treatment with Tac a major challenge for ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 169 publications
(211 reference statements)
0
3
0
Order By: Relevance
“…The dose adjustment not occur by just calculated the dose base on the BMI only, but the plasma level plays an important role. Machine-learning based approaches, statistic modelling, and genetic analyses, which have been proven to be effective in dose calculation recently in clinical practice (6,12,22). In the present study the medical doctors kept attention for the tacrolimus trough concentration level more than other parameters.…”
Section: Table (1): Areas Of Currently Practicing Doctor Specialty Ye...mentioning
confidence: 91%
See 2 more Smart Citations
“…The dose adjustment not occur by just calculated the dose base on the BMI only, but the plasma level plays an important role. Machine-learning based approaches, statistic modelling, and genetic analyses, which have been proven to be effective in dose calculation recently in clinical practice (6,12,22). In the present study the medical doctors kept attention for the tacrolimus trough concentration level more than other parameters.…”
Section: Table (1): Areas Of Currently Practicing Doctor Specialty Ye...mentioning
confidence: 91%
“…One brand of tacrolimus available in Sudan (Prograf® by Astellas), instead of that the patients who did the transplant operation out of Sudan came with different brands and therefore some of the physicians record abnormal trough plasma concentrations when they were shifted to the local available brand, which was a reasonable response among the pharmaceutical products as that differences on the impact of different pharmaceutical products observed also among the extended-release (ER-Tac) and immediate release (IR-Tac) (9,27). Bioequivalence between the generic or branded drugs and the original Prograf® has been shown in at least 10 publications, recently reviewed by Kocur et al with the exception of the granular formulation (Modigraf®), which showed a 23% and 18% higher mean for Cmax and AUC, respectively (12,(28)(29)(30). In the present study use of one brand exclude the impact of the drug formulation in the tacrolimus trough concentration among the population under study.…”
Section: Table (1): Areas Of Currently Practicing Doctor Specialty Ye...mentioning
confidence: 99%
See 1 more Smart Citation